To the question about the authors of the first railway station project in Harbin - Екатерина Глатоленкова (Проект Байкал, 2024)
The article deals with the architecture of the first railway station in Harbin built in the early XX century – the layout of the building, facade and interior solutions, urban design of the station. In order to identify the author of the project, the drawings of different variants made by the Technical Department of the Chinese Eastern Railway Company are analyzed.